Relationships Among MacArthur Subjective Socioeconomic Status, Ryff Psychological Well-Being, and the Technical Efficiency of Small-Scale Poultry Farmers in Nigeria - Ikuemonisan, Edamisan (Journal of Techno-Social, 2024)
This study investigated the interplay between MacArthur Subjective Socioeconomic Status (SSS), Ryff’s Psychological Well-Being (PWB), and Technical Efficiency (TE) among small-scale broiler farmers in Southwest Nigeria. Using a multistage procedure, 323 respondents were randomly selected. Analysis showed significant relationships between variables, with broilers per production cycle and feed intake positively impacting output. Temperature volatility had a negative effect on output due to increased stress in broilers. Age and cooperative membership were key factors influencing TE. The study also examined how subjective SES and PWB influenced innovative practices and risk-taking, ultimately enhancing TE. Incorporating Ryff’s PWB highlighted the positive impact of psychological well-being on TE through autonomy, personal growth, and purpose. Context-specific strategies and inclusive assessments are recommended to optimize technical efficiency in broiler farming, focusing on psychological well-being and subjective perceptions.